Korzyści z podejmowania regularnej aktywności fizycznej przez osoby starsze = The benefits of regular physical activity for the elderly - Kaźmierczak, U.; Radzimińska, A.; Dzierżanowski, M.; Bułatowicz, I.; Strojek, K.; Srokowski, G.; Zukow, W. (Journal of Education, Health and Sport, 2015)
Kaźmierczak U., Radzimińska A., Dzierżanowski M., Bułatowicz I., Strojek K., Srokowski G., Zukow W. Korzyści z podejmowania regularnej aktywności fizycznej przez osoby starsze = The benefits of regular physical activity for the elderly. Journal of Education, Health and Sport. 2015;5(1):56-68. ISSN 2391-8306. DOI: 10.5281/zenodo.13935 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%281%29%3A56-68 https://pbn.nauka.gov.pl/works/524287 http://dx.doi.org/10.5281/zenodo.13935 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.06.2014. Revised 05.10.2014. Accepted: 25.12.2014. Korzyści z podejmowania regularnej aktywności fizycznej przez osoby starsze The benefits of regular physical activity for the elderly Kaźmierczak U.¹, Radzimińska A.¹, Dzierżanowski M.², Bułatowicz I.¹, Strojek K.¹, Srokowski G.¹, Zukow W.³ Katedra Fizjoterapii CM UMK w Toruniu 1Zakład Kinezyterapii i Masażu Leczniczego UMK CM w Toruniu ²Zakład Terapii Manualnej UMK CM w Toruniu 3Wydział Kultury Fizycznej, Zdrowia i Turystyki, Uniwersytet Kazimierza Wielkiego w Bydgoszczy Słowa kluczowe: regularna aktywność fizyczna, osoby starsze. Keywords: regular physical activity, elderly. Abstrakt W państwach rozwiniętych i rozwijających się coraz większą grupę społeczeństw stanowią seniorzy. Świadomość problemu spowodowała podjęcie powszechnej dyskusji ekspertów i praktyków z dziedzin medycznych na temat konieczności działań niezbędnych dla zapewnienia społeczeństwom pomyślnej starości. Od dawna wskazuje się, że brak aktywności ruchowej jest dla zdrowia niebezpieczny. Starzeniu się układu sercowo-naczyniowego towarzyszy dużo niekorzystnych zmian strukturalnych, czynnościowych i biochemicznych. Za typowe dla tego okresu zmiany uważa się osłabienie możliwości relaksacji włókien mięśniowych, co może być przyczyną rozkurczowej niewydolności serca. Trening zdrowotny – jest rodzajem aktywności fizycznej wykonywanej z powodów medycznych. Celem jest uzyskanie efektów fizycznych oraz psychicznych przeciwdziałających zmniejszaniu się zdolności adaptacyjnych organizmu. Eksperci przekonują osoby starsze o korzyściach płynących z aktywnego fizycznie stylu życia. Bogate piśmiennictwo poruszające tematykę medycznych aspektów procesu starzenia, mówi o niezaprzeczalnym znaczeniu ruchu dla toczących się w ludzkim ciele procesów inwolucyjnych. Aktywność fizyczna odpowiednio dozowana jest w stanie wyraźnie zmniejszyć negatywny wpływ tych zmian i jak najdłużej pozwolić utrzymać zdrowie fizyczne, psychiczne i społeczne. Zauważono, że systematycznie dozowany wysiłek fizyczny zmniejsza ryzyko wystąpienia wielu chorób np. cukrzycy, miażdżycy, choroby niedokrwiennej serca. Liczne badania naukowe i bogate piśmiennictwo gerontologiczne przedstawiają najnowsze doniesienia specjalistów o tym, jak należy prawidłowo przygotować i prowadzić trening fizyczny z osobami starszymi. Ludzki organizm zaczyna starzeć się około 20-25 roku życia. Zmiany dotyczą wszystkich układów ciała. Najbardziej odczuwalne w życiu codziennym są te, które zachodzą w układzie krążeniowo-oddechowym i mięśniowo-szkieletowym. Trening fizyczny dla osoby starszej, aby był skuteczny i bezpieczny, powinien być skonstruowany i nadzorowany przez specjalistę. Abstract In developed and developing countries an increasing group of societies are seniors. Awareness of the problem has led to widespread discussion of experts and practitioners from the fields of medical devices on the need for the measures necessary to ensure that societies successful old age. For a long time, indicates that the lack of motor activity is dangerous to health. Aging of the cardiovascular system is accompanied by a lot of adverse structural changes and biochemical function. For typical of this period of change is believed to be weakening the possibility of relaxation of the muscle fibers, which may cause diastolic heart failure. Training of health-is a type of physical activity performed for medical reasons. The goal is to get mental and physical effects against reducing the adaptability of the body. Experts are finding older people about the benefits of a physically active lifestyle. Rich writing evocative theme of medical aspects of the aging process, speaks of undeniable importance for traffic in human flesh involutional processes. Physical activity appropriately dosed is able to clearly reduce the negative impact of these changes and as long as you can afford to maintain the physical, mental and social health. It was noted that systematically dosed exercise reduces the risk of many diseases, eg. diabetes mellitus, atherosclerosis, coronary heart disease. Numerous scientific studies and extensive external links gerontologiczne submit the latest reports of professionals about how to properly prepare and conduct physical training with the elderly. The human body begins to age about 20-25 years of age. The changes apply to all body systems. Most felt in everyday life are the ones that occur in the breathing cardiopulmonary and musculo-skeletal. Physical training for older persons, in order to be effective and safe, should be designed and supervised by a specialist.